The Effect of The Principal's Transformational Leadership and Work Motivation Toward Service Quality to Teachers of Private Islamic Junior High School (MTs) in Pontianak - Diana Fitriyah; Sukmawati Sukmawati; M. Chiar (JETL (Journal of Education, Teaching and Learning), 2019)
The problems that occur in the madrasahh are caused by the lack of quality of service in which the madrasahh principal leadership in Pontianak is not supported and the work motivation of teachers in improving education. The purpose of this study was to determine the effect of transformational leadership and work motivation of madrasahhh principals on the quality of service for private MTs in Pontianak. This study uses a quantitative approach and a type of descriptive research. The sample in this study were 70 teachers selected based on the sample random sampling technique. Data collection research was conducted by questionnaire and documentation. The results obtained from this study are that there is a significant effect between transformational principals' leadership and work motivation on service quality to Pontianak MTs teachers.